2019
DOI: 10.1186/s13643-019-1242-y
|View full text |Cite
|
Sign up to set email alerts
|

Methods and efficacy of extracellular vesicles derived from mesenchymal stromal cells in animal models of disease: a preclinical systematic review protocol

Abstract: BackgroundOver the past decade, mesenchymal stromal cells have been increasingly investigated for their therapeutic potential in several different illnesses. However, cell therapy can be limited by potentially serious adverse events including cell embolus formation and tumorigenesis. Importantly, the protective effects of mesenchymal stromal cells are largely mediated by paracrine mechanisms including release of extracellular vesicles. This systematic review intends to synthesize the current knowledge of mesen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Considering that the MSC-dependent mechanism of action is anchored in its secretome [42], a cogent argument can be made that the best cell therapy is done without any cells, but rather using elements of the secretome, such as components derived from extracellular vesicles such as exosomes [43]. Indeed, characterization and translational development of MSC-derived exosomes [44,45] and related extracellular vesicles are of great interest [46,47].…”
Section: Culture-adapted Mscs Meeting the 2006 International Society Formentioning
confidence: 99%
“…Considering that the MSC-dependent mechanism of action is anchored in its secretome [42], a cogent argument can be made that the best cell therapy is done without any cells, but rather using elements of the secretome, such as components derived from extracellular vesicles such as exosomes [43]. Indeed, characterization and translational development of MSC-derived exosomes [44,45] and related extracellular vesicles are of great interest [46,47].…”
Section: Culture-adapted Mscs Meeting the 2006 International Society Formentioning
confidence: 99%
“…In our recent comprehensive systematic scoping review of methods and outcome reporting in all preclinical studies of MSC-derived EVs, a total of 208 studies were identified [ 19 , 20 ] and an updated search conducted December 2018 identified 284 additional records that underwent screening for potential relevance and eligibility, identifying 113 additional studies. Amongst these 321 studies, four addressed GVHD treatment and/or prevention and were included in the quantitative and in-depth analysis described in this report (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We identified eligible studies from a comprehensive systematic scoping review performed in May 2018 and updated in December 2018 [ 20 ] (registered April 12, 2019 on PROSPERO at www.crd.york.ac.uk/prospero , protocol: CRD42019123918). In brief, this larger scoping review included all studies using MSC-EVs in preclinical animal models of disease, organ injury, tumor growth or altered immune response.…”
Section: Methodsmentioning
confidence: 99%
“…As more studies demonstrate that EV have an active and potentially therapeutic role in the body, as opposed to only a passive one (Joo et al, 2020;Tieu et al, 2019), it is anticipated that there will be more clinical trials focusing on their clinical potential rather than their role solely as biomarkers.…”
Section: Clinical Trialsmentioning
confidence: 99%